Surgical site infections after simultaneous pancreas kidney and pancreas transplantation in the Swiss Transplant Cohort Study. (October 2022) - Schreiber, P.W.; Laager, M.; Boggian, K.; Neofytos, D.; van Delden, C.; Egli, A.; Dickenmann, M.; Hirzel, C.; Manuel, O.; Koller, M.; Rossi, S.; Schmied, B.; et al.
Summary: Background: Among hospital-acquired infections, surgical site infections (SSIs) are frequent. SSI in the early post-transplant course poses a relevant threat to transplant recipients. Aim: To determine incidence, risk factors for SSI and its association with post-transplant outcomes and pancreas transplant (P-Tx) recipients. Methods: Adult simultaneous kidney–pancreas transplantation (SPK-T) and P-Tx recipients with a follow-up of at least 90 days were identified in the Swiss Transplant Cohort Study (STCS) dataset. Except for the categorization of SSIs according to Centers for Disease Control and Prevention (CDC) criteria, all other data were prospectively collected. Risk factors for SSI were investigated with logistic regression. A Weibull accelerated failure-time model was applied to address the impact of SSI on length of stay, correcting for transplant-related complications and delayed graft function. Findings: Of 130 transplant recipients, 108 SPK-Tx and 22 P-Tx, 18 (14%) individuals developed SSI within the first 90 days after transplantation. Deep incisional (seven, 38.9%) and organ/space infections (eight, 44.4%) predominated. In the majority of SSIs (11, 61.1%; two SSIs with simultaneous identification of fungal pathogens) bacteria were detected with Enterococcus spp. being most frequent. The median duration of hospitalization after transplantation was significantly longer in recipients with SSI (median: 26 days; interquartile range (IQR): 19–44) than in patients without SSI (median: 17 days; IQR: 12–25; P = 0.002). In multivariate analysis, SSI was significantly associated with increased length of stay and prolonged the duration of hospitalization by 36% (95% confidence interval: 4–79). Conclusion: SSI after SPK-Tx and P-Tx occurred at a frequency of 14%. Among pathogens, Enterococcus spp. predominated. SSI was independently associated with a longer hospitalization after transplantation.